The first Vietnam School of Earth Observation: Atmospheric Remote Sensing and Molecular Spectroscopy - Ha, Tran; Cuisset, Arnaud; Payan, Sébastien; Schwell, Martin; Té, Yao; Tomasini, Linda; Héraud, Yannick Giraud- (Vietnam Journal of Earth Sciences, 2019)
In this review paper, we give an introduction to molecular spectroscopy and its relation to atmospheric remote sensing and examples of recent developments in spectroscopic experimental techniques and modelling. Atmospheric retrieval techniques, based on radiative transfer theories and molecular spectroscopy as well as some atmospheric remote sensing missions using spectroscopic techniques are presented.